Application of HF discharge for nitriding of various surfaces - Gasilin, V.V.; Muratov, R.M.; Nezovibat'ko, Yu.N.; Taran, V.S.; Shvets, O.M. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The experimental results on nitriding of flat and inner surfaces of cylindrical specimens made from Ti and stainless steel (SS) are presented. The HF discharge was applied for nitriding with and without the application of an external magnetic field. The changes of specimens’ properties dependent on process conditions were investigated.